A conceptual framework for the social impact assessment of foreign workers influx on the social wellbeing of the second generation felda - Yahaya, Ibrahim; Wan Abd Aziz, Wan Mohd Amin (2017)
More recent media coverage and reports on foreign workers indicate the critical of the issue in the local setting. The influx of foreign workers in Malaysia is alarming. Most of them work in various employment sectors, in particular the plantation sector. In Malaysia, the largest plantation sector is the Federal Land Development Authority (FELDA). This paper intends to determine the social impact of foreign worker influx on the social wellbeing of the second generation FELDA. Also, this paper constructs the conceptual framework for a model of social impact research on the influx of foreign workers on the social wellbeing of the second generation FELDA. The primary data about the impact of foreign workers influxion on the social wellbeing of the second generation FELDA were collected from the questionnaire survey and focus group interviews that have been identified on giving a clearer picture of the current situation of foreign workers influx in FELDA plantation sector in Malaysia.